1990
DOI: 10.3382/ps.0690599
|View full text |Cite
|
Sign up to set email alerts
|

Heat-Stress Influences on Antibody Production in Chicken Lines Selected for High and Low Immune Responsiveness

Abstract: The effect of heat stress on antibody production to sheep red blood cells (SRBC) was investigated during three experiments using chicken lines selected over six generations for high (H) or low (L) plasma-antibody titer to SRBC after primary intramuscular immunization. The chickens were immunized 24 h after a heat-stress treatment (HS) of four periods of 30 min each at a temperature of 42 C with an intervening 30-min period at a temperature of 22 C. For the control treatment (CT), the chicks were handled the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
2
2

Year Published

1998
1998
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 21 publications
4
25
2
2
Order By: Relevance
“…Both primary and secondary antibody responses were significantly decreased when birds were reared under HS conditions. This response was similar to previous observations (Thaxton and Siegel, 1970;Donker et al, 1990;Bartlett and Smith, 2003). However, this is not always the case.…”
Section: Discussionsupporting
confidence: 92%
“…Both primary and secondary antibody responses were significantly decreased when birds were reared under HS conditions. This response was similar to previous observations (Thaxton and Siegel, 1970;Donker et al, 1990;Bartlett and Smith, 2003). However, this is not always the case.…”
Section: Discussionsupporting
confidence: 92%
“…Hai et al (2000) reported that the activities of digestive enzymes trypsin, chymotrypsin and amylase were significantly reduced when animals were kept at high temperature (32°C) conditions. Heat stress also decreases the serum and liver concentrations of vitamins (C, E and A) and minerals (Fe, Zn, Se and Cr) and also influence the immune response of poultry (Donker et al, 1990). There will be an increased rate of free radical production in the body due to an increase in body temperature (Altan et al, 2000(Altan et al, , 2003 and also by increase in whole body oxygen consumption (Sen, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…These differences were attributed to genetic variation among the different chicken lines in terms of their immunoglobulin production and catabolic rates (Regnier et al, 1980), immune system development rate (Parmentier et al, 1996) and blood corticostemne response during heat treatment (Siegel, 1987;Hester et al, 1996). Studies dealing with sex related differences in the immune response of chickens, on the other hand, are limited, and some workers reported either non-significant (Dunnington et al, 1987) or inconsistent (Donker et al, 1990) differences between male and female birds in their response to SFU3C. However, there are also indications from other studies that female chickens were capable of producing a higher antibody response to SRBC than male chickens (Van der Zjipp and Leenstra, 1980;Leitner et al, 1989).…”
Section: Reauita and Discussionmentioning
confidence: 88%